Factors Influencing Consumers to Repurchase Electric Vehicles: A Case of BYD - Pan, Bingxiong; Zhan, Xuegang; Phakdeephirot, Nutteera (Jurnal Ekuisci, 2025)
This research aims to verify the factors affecting the intention to repurchase electric vehicles in the context of BYD and to propose a strategic framework for the marketing of electric vehicles in China. This quantitative study employed a structured questionnaire to collect 419 BYD electric vehicle (EV) owners. Data analysis included descriptive statistics, reliability and validity tests, exploratory factor analysis, and structural equation modeling. The results indicate that functional, emotional, social, epistemic, and conditional values positively influence consumer satisfaction, which drives loyalty and enhances repurchase intention. Furthermore, this study encourages manufacturers to optimize product design, marketing strategies, and after-sales services while advising policymakers on incentive structures to support EV adoption and sustainable development goals.